Pemanfaatan Teknologi Informasi Dan Komunikasi Dalam Pembelajaran Al Qur’an dan Hadis Di MA Darul Muttaqin Baturaja - Daweri (UNISAN JURNAL, 2022)
Use of Information and Communication Technology (ICT) Media aims to find out the learning outcomes of Alqur'an Hadist at fourth grade students of MA Darul Muttaqin Baturaja with. The main problem in this research is: whether the use Information and Communication Technology of Media can improve learning outcomes Alqur'an Hadist About memorizing short letters at students MA Darul Muttaqin Baturaja? ". The type of research used is classroom action research, the subjects in this study are all students of MA Darul Muttaqin Baturaja which amounted to 32 students consisting of 19 men and 14 female students. The instrument used is the observation format of learning activities and Test Results Learning. The results of this study indicate that: There is an increase in student learning outcomes by ICT media that is on the first cycle the average score reached 81% students and on the second cycle The average value of students to be 91%. Based on this, it can be concluded that the using Information and Communication Technology of media can improve learning outcomes Alqur'an Hadist at students MA Darul Muttaqin Baturaja.